Effect of Increasing 6% Oil Corn Dried Distillers Grains with Solubles on Finishing Pig Growth Performance and Carcass Characteristics - Rachelle Lazaga; Katelyn N. Gaffield; Mikayla S. Spinler; Robert D. Goodband; Jordan T. Gebhardt; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 2,108 finishing pigs (PIC 337 × 1050; initially 54.7 ± 2.05 lb) were used in an 88-d study to investigate growth performance and carcass characteristics of pigs fed diets with increasing levels of 6% oil corn DDGS. Pigs were housed in mixed-sex pens, with 27 pigs per pen and 20 pens per treatment. Experimental diets were corn-soybean meal based with increasing levels of DDGS (0, 10, 20 and 30%) across four phases. The experiment was a randomized complete block design with barn and initial weight as blocking factors. Pens of pigs were weighed every two weeks to determine ADG, ADFI, and F/G. Three weeks prior to the end of the trial, three of the heaviest pigs in each pen were marketed. The remaining pigs were then marketed at the end of the study and carcass characteristics were also collected. Increasing DDGS decreased (linear, P < 0.005) ADG and worsened (linear, P < 0.001) F/G in both grower (54 to 168 lb) and finisher (168 to 295 lb) phases while average daily feed intake decreased (linear, P < 0.001) in the grower stage and tended (linear, P < 0.075) to increase in the finisher stage. Overall, final BW and ADG decreased (linear, P < 0.001) with increasing DDGS. However, average daily feed intake was not affected resulting in poorer (linear, P < 0.001) F/G. Caloric efficiency tended to increase (linear, P = 0.062) with increasing DDGS suggesting that our initial estimate of NE of DDGS (1,005 kcal/lb) was overestimated. There was a tendency (linear, P > 0.075) for decreased mortalities as DDGS increased, but no statistical difference in total mortality and removals was observed. Market weight, carcass yield, HCW and loin depth decreased (linear, P < 0.05) with increasing DDGS in the final marketing event, but backfat depth tended to decrease (quadratic, P = 0.076) and percentage lean tended to increase (quadratic, P = 0.058) as DDGS increased up to 20%; however, then reversed when DDGS inclusion further increased to 30%. Additionally, a subset of pigs (three barrows per pen from one of two research groups) was sampled at the first marketing event for determination of carcass characteristics and iodine value (IV). Market weight, carcass yield, and HCW decreased (linear, P ≤ 0.020; Table 5) with increasing DDGS. There were no differences in backfat depth, loin depth, or percentage lean between treatments during the first marketing event. Carcass IV increased (linear, P < 0.001) with increasing DDGS, ranging from 62.6 mg/g for pigs fed the diet without DDGS to 71.3 mg/g for pigs fed 30% DDGS. In conclusion, increasing 6% oil corn DDGS decreased ADG, market weight, carcass yield and HCW and increased IV. Thus, the reduction in diet cost with added 6% oil DDGS needs to offset the decreased growth performance to be economically justified and needs to be evaluated on a case-by-case basis.
Keywords: Dried distiller’s grains with solubles; growing pigs; iodine value; oil